Las explotaciones agropecuarias en los albores de la expansión cafetalera - Alvarenga Venutolo, Patricia (Revista de historia., 1986)
The article discusses changes in agricultural investment during the early development of coffee cultivation. The study focuses on the party of the province of Heredia wich is within the Central Valley. To explain economic change in the region, social sectors involved in various productive units from the late 18